(PHBS) Pada Masa Pandemi Covid-19 Untuk Mendukung Gaya Hidup Sehat Masyarakat Di Rw 05 Kelurahan Kampung Dalam Kecamatan Senapelan Kota Pekanbaru - Chairil, Chairil (LPPM UMRI, 2021)
Background: The spread of Covid-19 has now become a pandemic outbreak in Indonesia. The emergence of this disease outbreak encourages the importance of implementing PHBS. Implementing PHBS properly can help prevent Covid-19 and support a healthy lifestyle during this Covid-19 pandemic. Objective: To find out the description of Clean and Healthy Lifestyle (PHBS) during the Covid-19 pandemic to support a healthy lifestyle. The method used was the counseling lecture for 6-8 people. It was held from September 10 to September 20 in RW 05, Kampung Village in Senapelan District, Pekanbaru City. This population amounted to 203 families with the number of samples taken partly from the total population with the number of respondents used was 67 respondents. The sampling technique used is the Simple Random Sampling technique. The instrument used is a questionnaire. The results of the service in the category of good PHBS are 35 respondents (52.2%), while people who have poor PHBS are 32 respondents (47.8%). Conclusion: More efforts are needed for cooperation in RW 05, Kampung Village in Senapelan Subdistrict, Pekanbaaru City, that the community currently does not understand PHBS during the pandemic.